The Subfornical organ and limbic system of albino rats - Daryanto Daryanto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1993)
The objective of this study is to provide an account of anatomically connections between the subfomical organ and limbic system, using an immunofluorescent study with single fluorescent labeling tracer DAPI (4'-6-diamidino-2-phenylindol dihydrochloride), on seven adult albino rats of Wistar strain weighing between 250 - 350 g.The result of this study revealed that the subfomical organ, anatomically connected to the limbic system.Key Words: subfomical organ - limbic system - DAPI - albino rat - inunUnofluorescent